Exhaust assessment of a European Volumetric Neutron Source (EU-VNS) using SOLPS-ITER - S. Wiesen; Ch. Bachmann; M. Siccinio; J. Boscary; C. Bourdelle; M. Coleman; G. Federici; F. Maviglia; R. Neu (Nuclear Materials and Energy)
EUROfusion considers a volumetric neutron source (EU-VNS) to generate a neutron wall load of about 0.5MW/m2 to qualify tritium breeding blankets early in support of EU-DEMO that mitigates the risk of a late testing for required nuclear technology. The envisaged small-scale R=2.5m D-beam/T-target driven fusion device (Pfus≈30MW) must exhaust helium particles and dissipate sufficient energy from the large auxiliary power required (Paux≈50MW) entering in large parts the edge. A SOLPS-ITER assessment indicates that with argon seeding a finite divertor operational window exists allowing to avoid core dilution by helium and to reduce the peak heat-flux density below 10MW/m2. It is shown that an extra constraint of Zeff<2−3, required to sustain good core performance to produce the required amount of fusion neutrons, can also be met if the Greenwald-fraction fGW≈0.5 is maintained with total T-throughputs at about half the ITER value. It is reasoned that for a EU-VNS design study the exhaust operational window can be enlarged by choosing other seeding species like Krypton, refining the balance between pellet- to gas-fuelling, and integrated core-edge modelling.